Hereditary Motor and Sensory Neuropathy IIB - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The clinical and electrodiagnostic features of 10 adults in a family with axonal, autosomal dominant, hereditary motor and sensory neuropathy (HMSN IIB), with linkage to chromosome 3q, are reported from Washington University School of Medicine, St Louis, MO.